If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(x + 4) = 9 Reorder the terms: -10(4 + x) = 9 (4 * -10 + x * -10) = 9 (-40 + -10x) = 9 Solving -40 + -10x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + -10x = 9 + 40 Combine like terms: -40 + 40 = 0 0 + -10x = 9 + 40 -10x = 9 + 40 Combine like terms: 9 + 40 = 49 -10x = 49 Divide each side by '-10'. x = -4.9 Simplifying x = -4.9
| -11=17x-28 | | 5(8x+8)-2(2-7x)=12+55x | | 48y-63=37y+55 | | x-1.5y=-3 | | 16=10+3m | | 8y+1=-31 | | 4x^2+18x= | | 7(2+x)=3x+1 | | -6(k-2)-(-7k+1)=3 | | .5x-12=-14 | | 2y-6+4y-8=0 | | (x+2)+(27+x)=163 | | ln(x)-ln(x-1)=ln(x+3)-ln(x+5) | | 7y-(11-4y)=6 | | 43=26+e | | -2a+5a-13+12= | | 8.50t=51 | | 18+3-2y=5y+3y | | y=17(-3)-28 | | -5/3 | | -7x+11=32 | | 2n+11=-23 | | 5xy+21x=36y+216 | | 2x^3+3x^2-32x+48=0 | | 24x+8=28x | | x^2+y^2+14x-10y-7=0 | | (x+5)(2x-8)= | | -4=2z+10 | | 7x=16+6x | | 49x^2-42x+5= | | 43+4n=11n | | -8b+2+6a=9-30 |